Notes: (2) Discovery of a Short Cist containing a Beaker Urn at Boghead Farm, Pitsligo, Aberdeenshire - Edwards, Arthur J H (Proceedings of the Society of Antiquaries of Scotland, 1943)
The cist consisted of rough stone slabs and contained a fine specimen of a beaker urn, but no skeletal remains.